Transformational leadership style and talent management practices in improving employee engagement in the Malaysian public sector: the mediating role of public service motivation - Zahari, Norfadhillaton (2023)
This thesis aims to examine the factors that influence employee engagement in the context of Malaysian public service. It focuses on three main concepts: transformational leadership, talent management practices, and public service motivation. The concept of employee engagement has become of great interest among researchers and practitioners due to its significant impact on organisational performance. The role of leadership, talent management practices and public service motivation are becoming crucial, especially in this volatile, uncertain, complex, and ambiguous world. Leaders must express understanding, concern, and empathy toward employees and their needs. This study is timely as it was conducted during the global pandemic crisis when the job demands of public servants have increased rapidly. Based on Job Demands-Resources Theory, high job demands will undermine employee engagement due to mental, emotional, and physical exhaustion. Therefore, examining public servants' behavioural and motivational factors during this time is crucial since they serve as frontline workers to benefit people and the nation. This study has shed light on how to engage public servants in the Malaysian public service to bring out their greatest potential at work. This is a cross-sectional study that employed the quantitative method approach. A questionnaire was designed to examine the associations between the proposed variables. The sample of this study comprised 318 Administrative and Diplomatic Officers currently serving the Malaysian public service. Both pre-test and pilot studies were conducted to assess the validity, language, and relevancy of the questions included in the questionnaire. In this study, Statistical Package for Social Sciences Statistics version 27 and structural equation modelling: Smart PLS 3 were used as analysing tools to assess the measurement and structural model in this study to test the relationship between the variables and the impact of the proposed model on employee engagement. The result showed that talent management practices, self-perceived transformational leadership style and public service motivation have a positive relationship with employee engagement and that public service motivation mediates talent management practices – employee engagement relationship and self-perceived transformational leadership style – employee engagement relationship. Overall, the data suggested that the public sector needs to develop talent management practices and employee resources to improve employee engagement.